Does ownership matter? Japanese multinationals in Europe (Clarendon Press, 1994)
The dramatic rise of Japanese foreign direct investment (FDI) in Europe in the 1980s has stimulated enormous interest among scholars, policy-makers, and managers eager to understand the real significance of the 'Japanese challenge'